Mergers with a special purpose acquisition company (SPAC) - Conde Granados, Jorge L. (2021)
After almost two years since the outbreak of the pandemic and thanks to mass vaccination, economic reactivation has today more chances of success, hence companies are resuming their projects, including mergers and acquisitions. Furthermore, in the last three years, the international business and legal markets have been positively surprised by the increased use of a not-so-new business model: the Special Purpose Acquisition Company (SPAC), a type of company that first appeared in the 1980s. In the past three years, SPACs have been broadly used by private companies seeking to go public . This paper examines this matter.